2010
DOI: 10.3109/01460862.2010.528644
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Challenges in Families of Children with Autism: A Pilot Study

Abstract: A pilot study was conducted using a focus group interview with parents of children with autism to provide parents with the opportunity to express their concerns related to parenting a child with autism and to discuss strategies parents can use to manage these challenges. Parents' desire and need for information related to autism is evident. Parents' identified supports and resources in need of expansion and development to assist with their child's needs. These findings support previous research with families c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
6
43
0
Order By: Relevance
“… 35 , 43 In addition to these financial strains, inaccessibility or insufficiency of financial support was also reported. 36 , 50 , 51 Indeed, these financial problems increased the level of stress and worry in parents, with several paying for treatments out-of-pocket or taking multiple loans. 39 , 43 One parent in a study went to the extent of mortgaging the house to pay for treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 , 43 In addition to these financial strains, inaccessibility or insufficiency of financial support was also reported. 36 , 50 , 51 Indeed, these financial problems increased the level of stress and worry in parents, with several paying for treatments out-of-pocket or taking multiple loans. 39 , 43 One parent in a study went to the extent of mortgaging the house to pay for treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Parents described accepting the diagnosis and their child for who they were and focusing on what could be done. 15 , 32 , 49 , 55 57 The terms “doing all you can” 55 and “never give up” 50 depicted the pragmatism and perseverance parents had as they channeled all their strength and time to improve the child’s condition. 57 59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information technology has increasingly become part of daily life for many people, and newer studies show that the Internet is an important source of information for parents who are facing health issues or other special circumstances with regard to their children (Blackburn & Read, 2005;Hall & Graff, 2010;Parette, Meadan, Doubet, & Hess, 2010;Skinner & Schaffer, 2006;Zaidman-Zait & Jamieson, 2007).…”
Section: Implication For Practicementioning
confidence: 99%
“…The coping strategies parents used to deal with their child's autism included support from family and friends, joining support groups, connecting with other parents of children with autism, the use of service providers, advocacy and support groups and religion (DeMeyer, 1979;Gray, 2003;Hall & Graff, 2010). Studies also found significant associations between greater use of active-avoidance coping strategies with higher levels of depression, stress, and parenting stress (Paynter et al, 2013).…”
Section: Introductionmentioning
confidence: 89%